Inferred gas hydrate and permafrost stability history models linked to climate change in the Beaufort-Mackenzie Basin, Arctic Canada - J. Majorowicz; J. Safanda; K. Osadetz (Climate of the Past, 2012)
Atmospheric methane from episodic gas hydrate (GH) destabilization, the "clathrate gun" hypothesis, is proposed to affect past climates, possibly since the Phanerozoic began or earlier. In the terrestrial Beaufort-Mackenzie Basin (BMB), GHs occur commonly below thick ice-bearing permafrost (IBP), but they are rare within it. Two end-member GH models, where gas is either trapped conventionally (Case 1) or where it is trapped dynamically by GH formation (Case 2), were simulated using profile (1-D) models and a 14 Myr ground surface temperature (GST) history based on marine isotopic data, adjusted to the study setting, constrained by deep heat flow, sedimentary succession conductivity, and observed IBP and Type I GH contacts in Mallik wells. Models consider latent heat effects throughout the IBP and GH intervals. Case 1 GHs formed at ~0.9 km depth only ~1 Myr ago by in situ transformation of conventionally trapped natural gas. Case 2 GHs begin to form at ~290–300 m ~6 Myr ago in the absence of lithological migration barriers. During glacial intervals Case 2 GH layers expand both downward and upward as the permafrost grows downward through and intercalated with GHs. The distinctive model results suggest that most BMB GHs resemble Case 1 models, based on the observed distinct and separate occurrences of GHs and IBP and the lack of observed GH intercalations in IBP. Case 2 GHs formed >255 m, below a persistent ice-filled permafrost layer that is as effective a seal to upward methane migration as are Case 1 lithological seals. All models respond to GST variations, but in a delayed and muted manner such that GH layers continue to grow even as the GST begins to increase. The models show that the GH stability zone history is buffered strongly by IBP during the interglacials. Thick IBP and GHs could have persisted since ~1.0 Myr ago and ~4.0 Myr ago for Cases 1 and 2, respectively. Offshore BMB IBP and GHs formed terrestrially during Pleistocene sea level low stands. Where IBP is sufficiently thick, both IBP and GHs persist even where inundated by a Holocene sea level rise and both are also expected to persist into the next glacial even if atmospheric CO2 doubles. We do not address the "clathrate gun" hypothesis directly, but our models show that sub-IBP GHs respond to, rather than cause GST changes, due to both how GST changes propagates with depth and latent heat effects. Models show that many thick GH accumulations are prevented from contributing methane to the atmosphere, because they are almost certainly trapped below either ice-filled IBP or lithological barriers. Where permafrost is sufficiently thick, combinations of geological structure, thermal processes and material properties make sub-IBP GHs unlikely sources for significant atmospheric methane fluxes. Our sub-IBP GH model histories suggest that similar models applied to other GH settings could improve the understanding of GHs and their potential to affect climate.